Efficient utilization of oxygen-vacancies-enabled NiCo2O4 electrode for high-performance asymmetric supercapacitor. (20th July 2018) - Sun, Dongsheng; Li, Yonghe; Cheng, Xiaopeng; Shi, Huifeng; Jaffer, Saddique; Wang, Kuan; Liu, Xianqiang; Lu, Junxia; Zhang, Yuefei
Abstract: The pseudocapacitive materials, like spinel NiCo2 O4 (NCO), that use Faradaic reactions to store charge have been widespread paid attention for supercapacitors application. So, it is a basic fundamental guideline that the preparation of higher-performance pseudocapacitive materials depends on achieving and accelerating more Faradaic reactions in the aspect of electrodes. In this work, based on the mentioned principle, we report a facile method that could significantly promote the capacity of NiCo2 O4 nanoelectrode through annealing precursor nanowires (NWs) in different volume ratios of N2 and O2 condition. The pristine NCO (VN2 : VO2  = 0:1) only exhibited inferior performance with a specific capacitance of 0.88 F cm −2 (338.5 F g -1  at 2 mA cm −2 ) and capacitive retention of 54% from 2 to 30 mA cm −2 . While, for a comparison, the highest comprehensive performance of NCO-9 (VN2 :VO2  = 9:1) electrodes delivered superior specific capacitance of 3.8 F cm −2 (1461 F g -1  at 2 mA cm −2 ), excellent rate retention of 77% and good cycling stability. These boosted pseudocapacitive properties both in capacity and rate capability are attributed to the severe oxygen vacancy defects introduced in nitrided NCO NWs. The involving richness-enabled oxygen defects significantly enhance the electron/ions transportation, and then efficiently alter the well-known capacitive surfacial reaction into bulk pattern in the charge-discharge cycles. This dramatically increased electron/ions kinetics and electrochemical cites for Faradaic reactions. These results provide a deep insight into correlating oxygen vacancies induced structural and chemical evolution on enhanced capacitive performances of redox-active-NiCo2 O4 materials.